The Influence of Product Quality on Purchase Interest of Mie Gacoan Pancing among Management Students at Medan State University - Panjaitan, Rona A. P.; Lubis, Muthiah Balqis; Jannah, Raihanatul; Fazira, Laila Erra; Siregar, Zulkarnain; Khaira, Imamul (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
Business competition in the current era is increasingly fierce in the food business sector, companies are constantly required to survive and continue to excel in the competition. Purchase interest is one of the factors that influences a company to gain profits and survive. The object of this research is Mie Gacoan Pancing (Medan). Mie Gacoan is a spicy noodle restaurant that is popular and widely known among the public today, especially among young people. This research aims to analyze product quality on purchasing interest among Mie Gacoan consumers. This is because the noodles produced have a distinctive and spicy taste so that young people are interested in trying and consuming them. The method used in this research is a quantitative descriptive method with primary data types. In this study, the population that the researchers used was UNIMED students. Meanwhile, the sample used in this research was 30 UNIMED students who had consumed Gacoan Noodles and were willing to fill out the questionnaire provided by the researchers. The technique for taking data analysis uses the questionnaire method and then the results are processed using the SPSS application program. The results of this research state that product quality influences consumers' buying interest in Mie Gacoan Pancing (Medan).